2021
DOI: 10.1186/s12862-021-01790-0
|View full text |Cite
|
Sign up to set email alerts
|

Localized environmental heterogeneity drives the population differentiation of two endangered and endemic Opisthopappus Shih species

Abstract: Background Climate heterogeneity not only indirectly shapes the genetic structures of plant populations, but also drives adaptive divergence by impacting demographic dynamics. The variable localized climates and topographic complexity of the Taihang Mountains make them a major natural boundary in Northern China that influences the divergence of organisms distributed across this region. Opisthopappus is an endemic genus of the Taihang Mountains that includes only two spatially partitioned specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 102 publications
0
25
0
Order By: Relevance
“…Previous studies have confirmed significant differentiation and variation between O. longilobus and O. taihangensis based on geographic distribution, morphological characteristics and DNA information [ 26 , 27 , 29 – 33 ]. Subsequently, Chai [ 28 , 34 ] used transcriptome data to reveal differentially expressed genes and screened DNA markers of the two species to further prove the differentiation and variation between the two species.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Previous studies have confirmed significant differentiation and variation between O. longilobus and O. taihangensis based on geographic distribution, morphological characteristics and DNA information [ 26 , 27 , 29 – 33 ]. Subsequently, Chai [ 28 , 34 ] used transcriptome data to reveal differentially expressed genes and screened DNA markers of the two species to further prove the differentiation and variation between the two species.…”
Section: Discussionmentioning
confidence: 75%
“…During the long-term evolution of Opisthopappus , the dramatic geological changes and significant topographical barriers of Taihang Mountains could limit the large-scale population expansion and gradually introduce heterogeneity within different populations of O. taihangensis and O. longilobus [ 28 ]. O. taihangensis and O. longilobus were likely diverged during the early Miocene under a strengthening East Asian monsoon [ 29 ]. Subsequently, the dramatic climatic transformation and complex topography of the Taihang Mountains further promoted differentiations between the two species and their populations [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The whole O. longilobus plant is fragrant because of the substantial abundance of aromatic oil. Moreover, from June to September (i.e., the flowering period), it produces white flowers ( Guo et al., 2013 ; Wang, 2013 ; Jia and Wang, 2015 ; Ye et al., 2021 ). Many recent studies on O. taihangensis and O. longilobus focused on genetic diversity and genetic structure, tissue culture, community characteristics, and antioxidant and antibacterial compounds ( Guo et al., 2013 ; Chai et al., 2018 ; Zhang et al., 2018 ; Ye et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%